IDENT IFIKASI ARAH REMBESAN DAN LETAK AKUMULASI LINDI DENGAN METODE GEOLISTRIK RESISTIVITAS KONFIGURASI WENNER ~ SCHLUMBERGER DI TPA TEMESI KABUPATEN GIANYAR - I K PUTRA; M.S. Mahendra; I.P.G. Ardhana (ECOTROPHIC : Jurnal Ilmu Lingkungan (Journal of Environmental Science), 2012)
Garbage Dump (GD) of Temesi which is located at Temesi village within 6.5 km south east of Gianyar city, which is geographically located at a point 8°33 south latitude and 115Q east longitude with an altitude ± 191 - ± 196 meters above sea level. The area of GD of Temesi about 4 ha, by limitation; North: field rice and population residences; East: field rice; South: field rice and West: field rice. GD of Temesi Gianyar has been collecting garbage about 198.52 m2 /day. GD of Temesi operates with open dumping, so that the leachate from garbage to pollute the enviorment and shallow ground water around the GD. This study ms conducted to know the direction of seepage and location of point accumulation of leachate at GD of Temesi Gainyar. This study was conducted with measuring soil layer values at GD of Temesi Gianyar, was taken eight tracks measurement. The method used in this study by using the geoelectric resistivity with Wenner configuration and Schlumberger configuration. The eight tracks are taken represent the overall of the soil layer condition in GD of Temesi Gianyar. The result of study showed that the tracks 1st, 2nd, 3rd, 4th, 5th, 6th, and ih was indicated that leachate seep on area in each tracks, however, in 8th tracks was not identified of leachate (8th tracks is located far from the GD and it's contours are higher than the tracks of garbage). Value of leachate resistivity ranged from 3.98 - 8.91 nm with a depth ranging from 1.55 - 6.91 meters. Most of leachate spread to southward of GD as far as more than 400 meters. Accumulated of leachate widely available at a distance of 20, 50, and 400 meters to the south of the GD of Temesi. The main factor is the south of the GD has a lower contour. Another factor affecting the leachate seeped into the south is the present of some field irrigation water from north to south across a stack of garbage.